Overweight and obese children have lower cortisol levels than normal weight children. (30th December 2013) - Kjölhede, E Allansson; Gustafsson, PE; Gustafsson, PA; Nelson, N
Abstract Aim The stress hormone cortisol is vital to survival, and a disturbed circadian rhythm can be deleterious to health. However, little is known about cortisol levels in healthy children. The aim of this study was to examine cortisol levels in relation to body mass index (BMI), age and sex. Methods Salivary samples were collected in early morning, late morning and evening, on four consecutive days, from 342 children aged 6–12 years using Salivette® tubes. Samples were analysed using a commercial enzyme immunoassay (EIA). School nurses measured the children's height and weight, and these measurements were used to calculate their BMI. Results The children displayed a circadian rhythm in cortisol secretion, with morning zeniths and evening nadirs. Average cortisol levels in early morning, late morning and evening were significantly lower in overweight and obese children than in their normal weight counterparts. Cortisol levels did not vary significantly with age or sex. Conclusion Our findings may suggest cortisol suppression in overweight and obese children. We found no evidence that sex or age influences cortisol levels. These findings highlight the need for further research on the relationship between stress and obesity in children.